Risk Management Efficiency in UK Non-Life Insurance Companies - LIU, YITING (2018)
Insurers are being exposed to huge adverse risk in current financial market, consequently, risk management turn out to be a competitive tool for them. The present study was designed to investigate current situation of risk management efficiency in UK non-life insurers, where the top five non-life insurers in UK: Aviva, RSA, Bupa, Direct Line and Allianz were selected as samples for both qualitative and quantitative analysis. Annual reports of the five sample companies were the only data source for the study. In qualitative part, risk exposures, risk management technics and strategies of the five sample companies were analysed through five aspects: operational risk, market risk, credit risk, liquidity risk and reputational risks. In quantitative part, DEA method and DEAP (version 2.1) software were applied to assess integrated risk management efficiency of the five sample companies. The results of qualitative part demonstrated that the five major risk exposures of the five non-life insurance companies in UK were under control during 2017, while, the risk control methods applied in the five insurers during 2017 were various. What’s more, without any exercisable plan for monitoring or controlling, reputational risk was considered as a minor risk by most of the insurers. As for the results obtained in quantitative section, risk management efficiency was increased in 2016, which seems to the result of great effort non-life insurance companies had made in 2016. While, risk management efficiency declined for all the five firms in 2017 because they contribute great amount of capital to intangible assets, which appears to be risky for insurers. Finally, the suggestions for non-life insurance companies were provided and exercisable plan for improving reputational risk was given, for example, risk quantifying measurement and SCR (solvency capital requirement) strategy applied by RSA (Royal & Sun Alliance) tend to be useful methods to increase efficiency of risk management. For further study, more sample companies should be analysed based on multiple data sources to gain more reliable results. Besides, it is suggested to have deeper studies about how the application of quantitative measurement approach in risk management affect the efficiency of risk management in non-life insurance companies.